METODE DAKWAH DALAM MENGATASI PROBLEMATIKA REMAJA - Aldiawan Aldiawan (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
This study is a qualitative study that attempts to collect data by means of theoretical approaches, both preaching theories, and psychological theories. With both approaches it seeks to reveal answers to the problem of how the method of preaching in overcoming adolescent problems. After conducting research, the most important findings of this study are formulated as follows: Da'wah method in overcoming adolescent problems starting from the material must be in accordance with the needs of adolescents easily understood and must be a problem solving problem faced by adolescents. The intended method is lecture, question and answer, discussion, uswatun hasanah (exemplary), and home visit (home visit).